Legal Innovation in Hindu Law: The Intersection of Tradition, Modernity, And Gender Justice in Contemporary India - Parineeta Goswami (European Economic Letters (EEL), 2025)
Historically embedded in ancient religious texts such as the Manu Smriti and the Dharma Shastras, Hindu law has experienced profound legal innovations in contemporary India. These innovations, shaped by the evolving demands of gender justice, human rights, and constitutional values, reflect a transformative journey from customary practices to statutory reforms. This paper critically examines key legal innovations in Hindu law, focusing on the reform of personal laws and inheritance rights, particularly those affecting women. The paper will first explore landmark judicial decisions such as Shah Bano v. Union of India (1985) and Vishaka v. State of Rajasthan (1997), which laid the foundation for gender justice within the framework of Hindu law. Further, the Hindu Succession (Amendment) Act, 2005, which granted daughters equal rights to ancestral property, serves as a significant legal milestone in redefining inheritance rights in Hindu law. This paper will delve into the motivations behind these reforms, examining how the Indian judiciary and legislature have blended traditional legal principles with modern constitutional mandates to address gender inequality. The paper will also analyze challenges in reconciling Hindu law's traditional principles with contemporary human rights standards, especially in cases involving marital rights, divorce, and maintenance. As Hindu law continues to evolve, the paper will reflect on how these innovations contribute to a broader understanding of legal pluralism in Asia, highlighting the intersection of religion, law, and social justice. This paper aims to contribute to the discourse on how traditional legal systems can adapt to modern needs without losing their cultural and religious essence by providing a nuanced analysis of Hindu law's legal innovation.